Novel Hybrid Organic–Inorganic Spin‐on Resist for Electron‐ or Photon‐Based Nanolithography with Outstanding Resistance to Dry Etching. (5th August 2013) - Zanchetta, Erika; Giustina, Gioia Della; Grenci, Gianluca; Pozzato, Alessandro; Tormen, Massimo; Brusatin, Giovanna
Abstract : A new spin‐on alumina‐based resist exhibits excellent performance in terms of both achievable lateral resolution and etch resistance in fluorine‐based non‐cryo‐cooled dry etching processes. The resist has selectivity greater than 100:1 with respect to the underlying silicon during the etching process, patternability with various lithographic tools (UV, X‐rays, electron beam, and nanoimprint lithography), and positive and negative tone behavior depending only on the developer chemistry.